2020
DOI: 10.1186/s12889-020-08742-1
|View full text |Cite|
|
Sign up to set email alerts
|

Seeking care in the context of social health insurance in Kenya and Ghana

Abstract: Background Social Health Insurance (SHI) is widely used by countries attempting to move toward Universal Health Coverage (UHC). While evidence suggests that SHI is a promising strategy for achieving UHC, low-income countries often struggle to implement and sustain SHI systems. It is therefore important to understand how SHI enrollees use health insurance and how it affects their health-seeking behavior. This paper examines how SHI affects patient decision-making regarding when and where to seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Household members [ 25 , 28 , 31 , 33 , 48 ]; people with access to a private subsidized health insurance program [ 34 ]; community members [ 46 ]; HIV+ pregnant women [ 36 ]; pregnant women [ 37 ]; poor women who had given birth [ 38 ]; community residents [ 39 ]; males and females aged 23 to 59 years [ 45 ]; patients exiting healthcare facilities [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Household members [ 25 , 28 , 31 , 33 , 48 ]; people with access to a private subsidized health insurance program [ 34 ]; community members [ 46 ]; HIV+ pregnant women [ 36 ]; pregnant women [ 37 ]; poor women who had given birth [ 38 ]; community residents [ 39 ]; males and females aged 23 to 59 years [ 45 ]; patients exiting healthcare facilities [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…This scoping review reports the different strategies (derived from the included studies) to strengthen the health system for attaining UHC in Africa. These strategies include those that fall under capacity building in health facilities, as well as developing and improving health infrastructure (e.g., training, supervising, and retaining healthcare workers, developing healthcare facilities) [ 19 , 24 , 27 , 30 , 35 , 42 , 49 ]; health information systems (health technology assessment) [ 29 , 41 ]; access to essential medicines (access to medicines and introducing African traditional medicine and traditional health practitioners into health systems) [ 23 , 26 ]; and health financing [ 17 , 18 , 20 , 21 , 22 , 25 , 28 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 43 , 44 , 45 , 46 , 47 , 48 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many enrollees had to make co-payments because they were unaware of the accreditation status of the provider's full benefits of SHI. The coverage should expand access to primary healthcare, both to public and private providers, as there seemed to be more confidence in the private sector ( 39 ). Another study in Ghana demonstrated that the NHIS resulted in increased health-seeking behavior from informal to formal providers.…”
Section: Resultsmentioning
confidence: 99%
“…For women, one common reason was due to lack of access to the enrollment card or card number, as the husband was the principal cardholder. Furthermore, coverage of healthcare centers by NHIF is not uniform and women limited in travel may not have convenient access to providers who ac-cept NHIF, 33 which may highlight why women in our cohort were more likely to present in a delayed fashion and directly to MTRH. The act of enrolling in NHIF is also a challenge for women.…”
Section: Nhif Coverage and Limitationsmentioning
confidence: 98%